Acceleration of Olfactory Receptor Gene Loss in Primate Evolution: Possible Link to Anatomical Change in Sensory Systems and Dietary Transition. (10th April 2018) - Niimura, Yoshihito; Matsui, Atsushi; Touhara, Kazushige
Abstract: Primates have traditionally been regarded as vision-oriented animals with low olfactory ability, though this "microsmatic primates" view has been challenged recently. To clarify when and how degeneration of the olfactory system occurred and to specify the relevant factors during primate evolution, we here examined the olfactory receptor (OR) genes from 24 phylogenetically and ecologically diverse primate species. The results revealed that strepsirrhines with curved noses had functional OR gene repertoires that were nearly twice as large as those for haplorhines with simple noses. Neither activity pattern (nocturnal/diurnal) nor color vision system showed significant correlation with the number of functional OR genes while phylogeny and nose structure (haplorhine/strepsirrhine) are statistically controlled, but extent of folivory did. We traced the evolutionary fates of individual OR genes by identifying orthologous gene groups, demonstrating that the rates of OR gene losses were accelerated at the ancestral branch of haplorhines, which coincided with the acquisition of acute vision. The highest rate of OR gene loss was observed at the ancestral branch of leaf-eating colobines; this reduction is possibly linked with the dietary transition from frugivory to folivory because odor information is essential for fruit foraging but less so for leaf foraging. Intriguingly, we found accelerations of OR gene losses in an external branch to every hominoid species examined. These findings suggest that the current OR gene repertoire in each species has been shaped by a complex interplay of phylogeny, anatomy, and habitat; therefore, multiple factors may contribute to the olfactory degeneration in primates.